An assessment of advertising effectiveness of Indian banks using Koyck model. Issue 4 (22nd March 2019) - Mulchandani, Ketan; Mulchandani, Kalyani; Attri, Rekha
Abstract : Purpose: The problem of differentiation and creating a unique selling proposition is higher in the banking sector, as, any new service or product introduced is very quickly imitated by the competitors. The benefits of advertising have been seen to have long-term effects on the firm's performance and debate is still on whether the expenses of advertising should be amortized or expensed immediately has been the area of concern for many years. The purpose of this paper is to carry out a comparative analysis of advertising effectiveness on private and public sector banks in India. Design/methodology/approach: This study has included 33 listed commercial banks out of 41 listed on S&P BSE 500. Out of 33 banks, 14 banks belong to private sector and 19 banks are public sector banks. Data are extracted for a period of 14 years from 2004 to 2017 from Ace Equity. In total, there are 462 firm-year observations. Interest income, operating income and return on assets are the accounting measures considered in this paper. All the variables are deflated by total assets at the beginning of the period. To assess the effect of advertising on financial measures, distributed lag model is used. Findings: The results of Koyck model suggest that it takes lesser time for private sector banks to see a significant change in interest income and return on assets with a change in advertising expenses whereas in case of operating income, the results achieved are opposite. Originality/value: This study may be useful from accounting point of view to find out whether advertising creates long-term or short-term impact on financial measures. The study would help in determining the number of years for which advertising expenses can be amortized. With the help of these results, it can be said that advertisement expenses can be capitalized and then expensed over coming years. This means, to some extent advertisement has some long-run impact on financial measures considered in the study. In order to achieve more robust results, this study can be performed on different sectors.